Labor exploitation in the Italian agricultural sector: the case of vulnerable migrants in Tuscany - Guidi, Caterina Francesca; Berti, Fabio (Frontiers in Sociology, 2023)
Labour exploitation of agricultural migrant workers is a well documented phenomenon by investigations and field research in several Italian regions, both in the North as and in the South. Despite the that agri-food excellencies of the "Made in Italy" brand are a source of pride for the Italian entrepreneurship, includinged the viticulture sector, evidence shows that many of these products are the result of different levels of illegal recruitment and labour exploitation. In this paper, the Authors analyse the impact of recent waves of vulnerable migrants entering the Italian labour market and present the results of an intensive qualitative field research, held in Tuscany between 2021 and 2022. Through 60 interviews to with exploited migrant workers and 40 interviews to with relevantprivileged stakeholders, the Authors focus on the recruitment process of vulnerable migrants into the agriculture sector and the labour conditions granted to them regardless of their particular migratory status. The paper concludes with the analysis of the peculiarities of the Tuscan case of study, characterized by the presence of a legal system of labour exploitation. 1 ha formattato: Italiano (Italia) ha formattato: Italiano (Italia) Codice campo modificato ha formattato: Italiano (Italia) Codice campo modificato 15